THE PATTERN OF NITROGEN RELEASE FROM SLOW RELEASE FERTILIZER UREA-ZEOLITEHUMIC ACID - Ganda Darmono Nainggolan; Suwardi Suwardi; Darmawan Darmawan (Jurnal Zeolit Indonesia, 2009)
Nitrogen is essential nutrient for plants, deficiency of nutrient causes plants could not growth normally. Nitrogen is easily lost from soil so to reduce his lost by forming fertilizers available in slow form (slow release). Some materials can be used to create a slow release of which having high cation exchange capacity (CEC). Zeolite and humic acid are materials which have a highest CEC so it make possible to use as a slow release materials. The study aimed to determine the rate and pattern of nitrogen release from mixture formulas Slow Release Fertilizer (SRF) and urea-zeolite and humic-acid (UZA) and comparing rate of nitrogen release with urea pril. The study conducted in laboratory with incubation experiment during 14th weeks. Determination ammonium and nitrate was conducted by extracting the soil with extractant hydrodistillation 0.1 N HCl + 1 N KCl. The result showed that a higher humic acid concentration was given on fertilizer causes a nitrogen release become ammonium and nitrate more slowly. SRF H5 (urea:zeolit, 70%:30% with humic acid of 5%) have a slowest nitrogen release rate rather than five types of Slow Release Fertilizer (SRF) formulas which containing a humic acid. However, SRF H1 and H3 fertilizer (with humic acid of 1% and 3%) have a most efficiency nitrogen release rate rather than five types of Slow Release Fertilizer (SRF) which is containing a humid acid.